2010
DOI: 10.1128/iai.01308-09
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Francisella asiatica with Tilapia ( Oreochromis niloticus ) Innate Immunity

Abstract: Members of the genus Francisella are facultative intracellular bacteria that cause important diseases in a wide variety of animals worldwide, including humans and fish. Several genes that are important for intramacrophage survival have been identified, including the iglC gene, which is found in the iglABCD operon in the Francisella sp. pathogenicity island (FPI). In the present study, we examined the interaction of wild-type Francisella asiatica and a ⌬iglC mutant strain with fish serum and head kidney-derived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 62 publications
(126 reference statements)
2
28
0
Order By: Relevance
“…1). The zebrafish spleen and kidney are major sources of phagocytes (54,59), the primary cell type infected by Francisella in mammals and fish (11,49). Since in mammals the active form of caspase 1 is secreted from cells (22), culture supernatants and cell pellet fractions were assayed separately.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). The zebrafish spleen and kidney are major sources of phagocytes (54,59), the primary cell type infected by Francisella in mammals and fish (11,49). Since in mammals the active form of caspase 1 is secreted from cells (22), culture supernatants and cell pellet fractions were assayed separately.…”
Section: Resultsmentioning
confidence: 99%
“…For infections, F. noatunensis colonies from 4-day-old CHAH plates were scraped into sterile TSBCD broth (Trypticase soy broth [30 g/liter; Sigma], 0.1% cysteine, 0.2% dextrose), vortexed, and grown overnight at 26°C with shaking (200 rpm). Bacteria were pelleted and diluted in sterile PBS to specific OD 600 (optical density at 600 nm) concentrations corresponding to approximate CFU/ml as previously determined (49). Heat killing of bacterial samples was conducted at 56°C for 1 h. Bacterial cells diluted to the appropriate concentrations in PBS were used to infect zebrafish spleen and kidney single-cell suspensions for 8 h at a multiplicity of infection (MOI) of 50.…”
Section: Methodsmentioning
confidence: 99%
“…This eventually results in release of the bacteria to the extracellular space through host cell lysis or in the formation of Francisella-containing vacuoles through interactions with the autophagic pathway (19). It has been suggested that F. noatunensis subspecies are also able to escape from phagosomes into the cytosol (20)(21)(22).…”
mentioning
confidence: 99%
“…Macroscopic and microscopic examination often reveals enlarged internal organs containing widespread multifocal white nodules (13,14,15,17,19,20,29). Moreover, F. asiatica has been found to be resistant to serum killing and can penetrate, replicate, and survive in tilapia head kidney-derived macrophages (THKDM) (31).…”
mentioning
confidence: 99%
“…are facultative intracellular pathogens, capable of replicating in macrophages and other various cell types in humans, rabbits, rodents, nonhuman primates, and fish. The bacteria may also exist as endosymbionts of amoebae and arthropods (1,2,7,26,31,34). Francisella asiatica and Francisella noatunensis are two recently described members of the genus that causes piscine francisellosis in a wide variety of fish species (19).…”
mentioning
confidence: 99%